Diabetes Mellitus and HIV Infection among Newly Diagnosed Pulmonary Tuberculosis Patients in the North West Region of Cameroon: A Cross-Sectional Study - Leonard Fonkeng Sama; Sidoine Sadjeu; Thibau Flaurant Tchouangueu; Solange Dabou; Georges Ful Kuh; Omer Bebe Ngouateu; Michel Noubom (International Journal of Clinical Practice)
Objective. To determine the prevalence rate of HIV and diabetes among tuberculosis (TB) patients and also the comorbidity rate. Design. Cross-sectional study. Setting. This study was carried out at the Tuberculosis Reference Laboratory, Regional Hospital Bamenda, North West Region of Cameroon, from January 2017 to December 2019. Participants. 1115 cases of pulmonary tuberculosis aged ≥14 years (mean 42.5 ± 15.28 years). Methods. Sputum samples collected were acid-fast stained and examined macroscopically as well as inoculated for culture. A chest X-ray was performed for further confirmation of TB diagnosis. After the TB diagnosis was done, fasting blood glucose, 2 h-PG test, HbA1c, and biochemical enzymatic tests were performed for the diagnosis of diabetes. Rapid strip test and enzyme-linked immunosorbent assay were used to diagnose HIV infection. Interventions. No intervention was done during the period of study. Outcome Measures. The prevalence of TB/HIV and TB/HIV/DM, signs and symptoms, imaging results, and bacteriology status among TB/HIV, TB/HIV/DM coinfected, and comorbidity cases. Results. Of 1115 participants, 38.57% had TB/HIV, and 5.83% had TB/HIV/DM. Among TB/HIV/DM cases, 20.39% had a cough for more than 2 weeks [p < 0.0001; OR (95%CI): 4.866 (3.170–7.404)], and 35.71% had a fever for at least 2 weeks [p < 0.0001; OR (95%CI): 7.824 (5.336–11.36)]. The majority of TB/HIV/DM patients (77.42%) had chest pain for at least 2 weeks [p < 0.0001; OR (95%CI): 114.3 (59.78–207.1)]. 7.41%, 14.18%, and 9.09% of TB/HIV/DM, respectively, had chest abnormality, positive smear, and positive culture (p = 0.018). Significant differences were observed between signs and symptoms, imaging results, bacteriology, treatment history for TB cases and those with HIV and/or DM, and those without HIV and/or DM coinfection and comorbidity. Conclusion. This study reports a high prevalence of DM comorbidity and HIV coinfection among active TB patients in the North West Region of Cameroon as well as TB/HIV/DM comorbidity.